Three Steps Towards More Effective Development Assistance - Jim Rose; Simon Hay (New Zealand Government, The Treasury, 2001)
There are three steps New Zealand can take to make its bilateral development assistance more effective in reducing poverty. These steps are `easy' because they are unilateral: they improve the effectiveness of development assistance without requiring changes in the politics or policies of developing countries. By far the most important of these three steps is to focus New Zealand's bilateral aid on those poor countries that are democracies pursing policies of market-led growth. One of the major findings of recent research is that development aid only reinforces what is already there. New Zealand should accept the developing countries as it finds them and pick and choose so that it helps those already helping themselves.
Keywords: D72; F35; O12; O2; P2; P3; P51; P52; 330; aid effectiveness; autocracy; democracy; development; New Zealand